A portable isometric knee extensor strength testing device: test-retest reliability and minimal detectable change scores of the Q-Force ӀӀ in healthy adults - Johanneke Hartog (BMC, 2021)
Abstract Background Although knee extensors are essential in daily activities (e.g. walking, climbing stairs), knee extensor strength is often not measured in clinical settings. Existing devices to test muscle strength are not always suitable to accurately measure the high forces of this muscle group. Therefore, a device to test muscle strength that is convenient, feasible, reliable, and valid in clinical settings is required. This study evaluated the reliability, responsiveness, and level of discomfort of the newly developed Q-Force ӀӀ (i.e. a portable device to measure isometric knee extensor strength) in healthy middle-aged and elderly adults. Methods Participants (n = 22) conducted two standardized test sessions on the Q-Force ӀӀ (five to ten days apart). Each session consisted of one familiarisation trial followed by three trials of peak isometric knee extension per each leg. Per trial, peak and mean knee extension force (N) and torque (Nm) were measured at 90° flexion. The level of discomfort was determined using a visual analog scale (VAS: 0-100). Intra Class Correlation (ICC, model: two-way mixed with absolute agreement), Standard Error of Measurement (SEM), and minimal detectable change (MDC) were determined. A repeated measures ANOVA was used to determine between-test variation. Results Excellent test-retest (ICC > 0.95) and inter-trial (ICC > 0.91) reliability for both legs were shown. No significant differences were found in peak and mean knee forces and torques between test and retest of both legs, indicating good test-retest reliability (P-value range: 0.360-0.538; F(1,21) range: 0.4-0.9). The SEM of the peak and mean forces and torques ranged from 28.0 to 30.4 N (6.0-6.8%) and from 9.2 to 10.4 Nm (6.4-7.7%), respectively. The MDC for these outcomes ranged respectively from 77.6 to 84.1 N (16.5-18.8%) and from 25.5 to 28.9 Nm (17.6-21.4%). The level of discomfort was low (median range: 7-10, IQR: 4-18). Conclusion The portable Q-Force ӀӀ is a comfortable, responsive, and relatively cheap device with excellent test-retest reliability. This device would be potentially suitable to measure isometric knee extensor strength in clinical settings.